Globální aspekty moderních metod vzdělávání - Liška, Václav; Nováková, Vladimíra (Univerzita Pardubice, 2009)
This article deals with the key role of education and research of Universities and describes the specific example how to increase knowledge of students and create the better conditions on the labourt market for them.
Keywords: Education; Research; university; knowledge; students